Knowledge, attitudes, and behaviors regarding sun protection, effects of the sun, and skin cancer among Turkish high school students and teachers - Engin Şenel; Iclal Süslü (Wolters Kluwer Medknow Publications, 2015)
Background/objective: The incidence of skin cancer has increased dramatically worldwide over the past decades, and adolescents are prone to exposing themselves to the harmful effects of the sun. Although there are plenty of studies assessing the knowledge level and behavior of adolescents regarding sun protection and skin cancer, to the best of our knowledge, this is the first study evaluating both adolescents and their teachers. This study aimed to evaluate high school students' and teachers' knowledge, attitudes, and behaviors regarding sun protection and skin cancer. Methods: A total of 396 students and 139 teachers from two high schools in Ankara, the capital of Turkey, were enrolled in the study. An anonymous questionnaire form was used to obtain the required data for our cross-sectional and nonrandomized study. Results: Male students stayed significantly longer in the sun than female students (p < 0.001). Only 41.8% of the students stated that they used a sunscreen when outside only in summer. This percentage was 81.9% for the teachers and is statistically higher than for the students (p < 0.001). We found no difference with regard to sex, however, a female predominance in sunscreen usage has been reported in the literature. Conclusion: Major information sources should be used more effectively to increase the knowledge level of the students.